O COMEÇO E O FIM DO MUNDO: estigmatização e exclusão social de internos da colônia do Bonfim - CÂMARA, Cidinalva Silva (2009)
This dissertation examines the social, political and stigmatized in connection with the compulsory isolation of men, women and children infected by leprosy (Mycobacterium leprae) in asylum-colony of Bonfim, in São Luís between the years of 1937 and 1965. Dealing with problems related to daily life of individuals there were hospitalized for structuring in asylum institution and impacts produced in their lives. Analyzing further, the extent to which the social construction of leprosy as a public health problem and the institutionalization of compulsory isolation of the patient contributed to the stigma and social exclusion of thousands of individuals in the whole country and particularly in Maranhão. It is considered that they were involved in such measures giving isolation, disputes of power based on knowledge about the disease and the patient, and impacts produced in their lives.